Immunotherapy in MSI/dMMR tumors in the perioperative setting: The IMHOTEP trial. Issue 10 (October 2022) - Coutzac, Clélia; Bibeau, Frederic; Ben Abdelghani, Meher; Aparicio, Thomas; Cohen, Romain; Coquan, Elodie; Dubreuil, Olivier; Evesque, Ludovic; Ghiringhelli, François; Kim, Stefano; Lesourd, Samuel; Neuzillet, Cindy; et al.
Abstract: Background: Immune checkpoint inhibitors (ICI) targeting Programmed death-1 (PD-1) have shown their efficacy in advanced MSI/dMMR (microsatellite instability/deficient mismatch repair) tumors. The MSI/dMMR status predicts clinical response to ICI. The promising results evaluating ICI in localized MSI/dMMR tumors in neoadjuvant setting need to be confirmed in MSI/dMMR solid tumors. The aim of the IMHOTEP trial is to assess the efficacy of neoadjuvant anti-PD-1 treatment in MSI/dMMR tumors regarding the pathological complete response rate. Methods: This study is a prospective, multicenter, phase II study including 120 patients with localized MSI/dMMR carcinomas suitable for curative surgery. A single dose of pembrolizumab will be administered before the surgery planned 6 weeks later. Primary objective is to evaluate the efficacy of neoadjuvant pembrolizumab according to pathological complete tumor response. Secondary objectives are to assess safety, recurrence-free survival and overall survival. Ancillary studies will assess molecular and immunological biomarkers predicting response/resistance to ICI. First patient was enrolled in December 2021. Discussion: The IMHOTEP trial will be one of the first clinical trial investigating perioperative ICI in localized MSI/dMMR in a tumor agnostic setting. Assessing neoadjuvant anti-PD-1 is mandatory to improve MSI/dMMR patient's outcomes. The translational program will explore potential biomarker to improve our understanding of immune escape and response in this ICI neoadjuvant setting.